Praktik Menulis Puisi pada Peserta Didik PKBM Ilmu Bunda Kota Bengkulu - Juwita Juwita; Supriyanto Supriyanto; Deffri Anggara (Universitas Dehasen Bengkulu, 2022)
The purpose of this community service is so that PKBM Ilmu Bunda Bengkulu students are able to write poetry. Implementation of Community Service activities by collaborating between Dehasen Bengkulu University lecturers and PKBM Ilmu Bunda Kota Bengkulu in order to provide socialization of the introduction of poetry writing literacy. This activity was carried out as an initial stage to see the response of the PKBM Ilmu Bunda Kota Bengkulu students in the learning process and apply it directly in the world of learning for students. Community Service Activities in the context of implementing the Tri Dharma of Higher Education in the Even semester of the 2020/2021 academic year have been carried out at the PKBM Ilmu Bunda in Bengkulu City. This activity is the result of a collaboration between a Physical Education Lecturer at the University of Dehasen Bengkulu with PKBM Sains Bunda regarding writing practice